Does intracranial pressure management hurt more than it helps in traumatic brain injury?. Issue 1 (12th January 2018) - Adams, Charles A; Stein, Deborah M; Morrison, Jonathan J; Scalea, Thomas M
Abstract : Traumatic brain injury (TBI) is the leading cause of death after traumatic injury. Raised intracranial pressure (ICP) is particularly associated with poor TBI outcomes, prompting clinicians to monitor this parameter, using it to guide therapies aimed at reducing pressures. Despite this approach being recommended by several bodies such as the Brain Trauma Foundation and the American College of Surgeons, the evidence demonstrating that ICP-guided therapy improves outcome is limited. The topic was debated at the 36th Annual Point/Counterpoint Acute Care Surgery Conference and the following article summarizes the discussants points of view along with a summary of the evidence. Level of evidence: Level III.